FEASIBILITY ANALYSIS OF COFFEE PROCESSING BUSINESS IN CIJAMBU SUMEDANG - Rina Indrayani; Herman Suwarman; Danny Aidil (Faculty of Economic and Business, University of Pasundan, 2023)
The increase of coffee consumption encourage a small scale enterprise, Cijambe Coffee to identify the current business performance to face the challenge. The research purposes are 1) to evaluate the feasibility of Cijambe Coffee business, 2) To interpreted the evaluation result in recommendation that help enterprise to decide the strategy. The research method is quantities and qualitative approach. The evaluation results: 1) the product has distinctive quality, 2) Technical factor is feasible in terms of producing good quality, 3) financially feasible that is proven by the parameters: NPV (IDR 2,350,000), PP (2.9 years), IRR (27.88%), and unit BEP (169.23 units), and the value of BEP ( Rp. 5,076,923.07), 4) Recommended strategy are : expanding market and production capacity with accurate forcast and strategy; the shifting of B to C into B to B market strategy or mix of both; acquiring business partners with good bargain and productive resources.